2022
DOI: 10.1021/acs.cgd.1c01348
|View full text |Cite
|
Sign up to set email alerts
|

Mono-, Di-, and Tetranuclear Manganese(II) Complexes with p-Phenylsulfonylcalix[4]arene Macrocycles as Ligand Antennas: Synthesis, Structures, and Emission Properties

Abstract: Three manganese(II) coordination compounds with a pphenylsulfonylcalix[4]arene (ppThiaSO 2 ) ligand were synthetized and are denoted as follows: [Mn II (ppThiaSO 2 )(DMF) 4 ] (1) (DMF = N,Ndimethylformamide), [Mn2II(ppThiaSO 2 )(DMF) 6 ] (2), and K-[Mn 4 II (ppThiaSO 2 ) 2 F] in the form of two pseudo-polymorphs (3a and 3b).Their electronic emission spectra were studied in the solid state at different temperatures and at various excitation wavelengths. All compounds (2, 3a, and 3b) except 1 present luminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It was shown that TCA-and SO 2 CA-based 3d and 4f metal complexes can exhibit not only attractive magnetic [28], but luminescence properties [32][33][34]. For a series of SO 2 CA-based manganese (II,III) complexes [35], green-red luminescence was revealed, related with prohibited d-d* electron transitions, thus evidencing the significant role of the electron structure of the macrocyclic ligand with respect to the observed physical properties of the complexes.…”
Section: Introductionmentioning
confidence: 94%
“…It was shown that TCA-and SO 2 CA-based 3d and 4f metal complexes can exhibit not only attractive magnetic [28], but luminescence properties [32][33][34]. For a series of SO 2 CA-based manganese (II,III) complexes [35], green-red luminescence was revealed, related with prohibited d-d* electron transitions, thus evidencing the significant role of the electron structure of the macrocyclic ligand with respect to the observed physical properties of the complexes.…”
Section: Introductionmentioning
confidence: 94%